Efficacy of physical activity interventions on psychological outcomes in refugee, asylum seeker and migrant populations: A systematic review and meta-analysis. (May 2021) - Purgato, Marianna; Richards, Justin; Prina, Eleonora; Kip, Ahlke; Del Piccolo, Lidia; Michencigh, Giulia; Rimondini, Michela; Rudi, Doriana; Vitali, Francesca; Carta, Mauro Giovanni; Morina, Nexhmedin; Schena, Federico; et al.
Abstract: Objectives: The role of physical activity (PA) in the promotion of mental wellbeing and prevention of psychological disorders in population groups at increased risk for mental health conditions, such as migrant populations, has never been systematically investigated. Methods: We conducted a systematic review and meta-analysis according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement. We searched the Cochrane Central Register of Controlled Trials (CENTRAL), Pubmed, Web of Science, SportDiscus. We included randomized (RCTs), controlled clinical trials (CCT), and pre-post intervention studies, that assessed the efficacy of PA interventions in migrants, compared with any types of controls. Results: We included 27 studies (4166 participants) (16 RCTs; 2 CCTs; 9 pre-post design) between 1997 and 2020. Meta-analysis showed a significant beneficial effect of PA over control conditions for general functioning (SMD -0.35, 95% CI -0.83 to −0.16; 400 participants), outcome expectancies (SMD -0.78, 95% CI -1.17 to −0.40; 118 participants), self-efficacy/coping (SMD -0.28, 95% CI -0.52 to −0.03; 269 participants), and psychological symptoms (SMD -0.48, 95% CI -0.88 to −0.08; 6 RCTs; 597 participants). Similar findings were produced by pre-post intervention studies (SMD -0.35, 95% CI -0.60 to −0.10; 7 studies; 302 participants). Conclusions: Migrant populations may benefit from PA interventions to improve psychological outcomes. Uncertainty remains about the best approach to promote PA in this population, and future research should consider the complex factors that characterize the migration experience. Highlights: Physical activity interventions are effective for several mental health conditions. There is no evidence on the benefit of physical activity for migrant populations. This review showed that physical activity is beneficial on wellbeing outcomes. Future research should consider migration variables as potential effect modifiers.